Computational Elucidation of a Role That Brønsted Acidification of the Lewis Acid‐Bound Water Might Play in the Hydrogenation of Carbonyl Compounds with H2 in Lewis Basic Solvents. Issue 48 (1st August 2017) - Heshmat, Mojgan; Privalov, Timofei
Abstract: Brønsted acidification of water by Lewis acid (LA) complexation is one of the fundamental principles in chemistry. Using transition‐state calculations (TS), herein we investigate the role that Brønsted acidification of the LA‐bound water might play in the mechanism of the hydrogenation of carbonyl compounds in Lewis basic solvents under non‐anhydrous conditions. The potential energy scans and TS calculations were carried out with a series of eight borane LAs as well as the commonly known strong LA AlCl3 in 1, 4‐dioxane or THF as Lewis basic solvents. Our molecular model consists of the dative LA‐water adduct with hydrogen bonds to acetone and a solvent molecule plus one additional solvent molecule that participates is the TS structure describing the cleavage of H2 at acetone's carbonyl carbon atom. In all the molecular models applied here, acetone (O=CMe2 ) is the archetypical carbonyl substrate. We demonstrate that Brønsted acidification of the LA‐bound water can indeed lower the barrier height of the solvent‐involving H2 ‐cleavage at the acetone's carbonyl carbon atom. This is significant because at present it is believed that the mechanism of the herein considered reaction is described by the same mechanism regardless of whether the reaction conditions are strictly anhydrous or non‐anhydrous. Our results offer an alternative to this belief that warrants consideration and further study. Abstract : Food for thought : Transition‐state calculations indicate the role that Brønsted acidification of water, due to Lewis acid complexation, might play in the mechanism of the hydrogenation of carbonyl compounds in Lewis basic solvents with H2 under non‐anhydrous conditions.